Christian Apophaticism in Jean-Luc Marion’s Early Works - Zachhuber, Johannes (Verbum Vitae, 2023)
In this article, I investigate Jean-Luc Marion’s early interpretation of Christian apophaticism with special reference to his reading of Pseudo-Dionysius the Areopagite. I observe that the most remarkable, but rarely noted, aspect of this interpretation is Marion’s avoidance of the typical derivation of Dionysius’ negative theology from the Platonic tradition. Instead, he places him in the tradition of the critique of idols in the Old Testament. I argue that this intuition should not be lightly dismissed as early Christian apophaticism was at least partly developed in the context of Christian polemic against pagan idolatry. If Christian apophaticism is understood against this background, Marion’s claim that it foreshadows the modern and postmodern critique of theism appears more plausible than his detractors have been willing to admit.